2021
DOI: 10.3390/tropicalmed6030115
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Environmental Determinants of Leptospirosis: A Retrospective Spatiotemporal Analysis (2004–2014) in Mahasarakham Province (Thailand)

Abstract: Leptospirosis has been recognized as a major public health concern in Thailand following dramatic outbreaks. We analyzed human leptospirosis incidence between 2004 and 2014 in Mahasarakham province, Northeastern Thailand, in order to identify the agronomical and environmental factors likely to explain incidence at the level of 133 sub-districts and 1,982 villages of the province. We performed general additive modeling (GAM) in order to take the spatial-temporal epidemiological dynamics into account. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Moreover, this infectious disease is considered endemic and a significant public health concern in Maha Sarakham province. In fact, between 2004 and 2014, Kosum Phisai district (where our study site was located) reported the second highest number of human cases in the province [ 27 ]. Thus, there may be a possibility that various animal species, including wild macaques, could play a potential role in leptospirosis animal reservoirs at this study site, as previous research suggested [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, this infectious disease is considered endemic and a significant public health concern in Maha Sarakham province. In fact, between 2004 and 2014, Kosum Phisai district (where our study site was located) reported the second highest number of human cases in the province [ 27 ]. Thus, there may be a possibility that various animal species, including wild macaques, could play a potential role in leptospirosis animal reservoirs at this study site, as previous research suggested [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, between 2004 and 2014, Kosum Phisai district (where our study site was located) reported the second highest number of human cases in the province [ 27 ]. Thus, there may be a possibility that various animal species, including wild macaques, could play a potential role in leptospirosis animal reservoirs at this study site, as previous research suggested [ 27 ]. It should be noted, however, that our results did not support a role of wild macaques in the transmission of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Leptospirosis outbreak in Mahasarakham Province is still a health issue, although the leptospirosis prevention and control seemed to have gained from the enhanced collaboration between the Public Health Department, the Livestock Department and the Tambon Administration Organization following the prevention strategy of 2011 [ 30 ]. However, there is a lack of linkages between departments to ensure comprehensive disease prevention activities.…”
Section: Discussionmentioning
confidence: 99%
“…Mayfield et al, 2017;Sahin et al, 2013). Specific geospatial models, such as geographically weighted regression or Kriging, can be used where data are spatially correlated (Mayfield, 2018a;Viroj et al, 2021).…”
Section: Ensemble and Hybrid Modellingmentioning
confidence: 99%